The Use of Hijaiyah Fun Card Media to Improve Early Childhood's Ability in Reading and Memorizing Hijaiyah Letters - Nur Hasana Alvi Syahrin; Masganti Sit (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
The ability to read and memorize Hijaiyah letters is one of the fundamental skills that need to be developed in early childhood as a foundation for learning the Qur’an. However, based on preliminary observations, children's ability to read and memorize Hijaiyah letters had not developed optimally. This study aimed to improve the ability of early childhood learners to read and memorize Hijaiyah letters through the use of Hijaiyah Fun Card media. The study is expected to provide an innovative learning medium for teachers in enhancing children's religious literacy skills. This research employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection stages. The participants were seven children aged 5–6 years in Group B. Data were collected through observation, documentation, and field notes. The findings revealed that the use of Hijaiyah Fun Card media improved children's ability to read and memorize Hijaiyah letters. In Cycle I, 57.14% of the children were categorized as Developing as Expected (MB), while 42.86% were categorized as Developing According to Expectations (BSH). After improvements were made in Cycle II, 57.14% of the children achieved the Very Well Developed (BSB) category, while 42.86% remained in the Developing as Expected (MB) category. The use of Hijaiyah Fun Card media was proven to increase children's learning interest, concentration, and ability to read and memorize Hijaiyah letters. Therefore, Hijaiyah Fun Card can be used as an effective alternative learning medium for teaching Hijaiyah letters in early childhood education.